Nonreciprocal vortex conversion and frequency shifting using light-driven chiral flexural waves - Zeng, Xinglin; Russell, Philip St. J.; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
We report nonreciprocal vortex conversion and frequency shifting via cork-screw-like chiral flexural phonons induced by forward Brillouin scattering in chiral photonic crystal fibre. A nonreciprocity factor greater than >13 dB is achieved.
CRIS-Team Scopus Importer:2023-11-24